2021
DOI: 10.1039/d1na00296a
|View full text |Cite
|
Sign up to set email alerts
|

Biobased superhydrophobic coating enabled by nanoparticle assembly

Abstract: Understanding biobased nanocomposites is critical in fabricating high performing sustainable materials. In this study, fundamental nanoparticle assembly structures at the nanoscale are examined and correlated with the macroscale properties of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…To bridge physical experiments and computer simulations, Olson et al recently reported a BD-MC simulation of nanoparticle aggregation in biopolymer matrices using an interparticle potential derived from in situ AFM measurement of surface forces in the HES and HEC solutions. 239 The new AFM-derived potential agrees well with the theoretical interaction model between silica nanoparticles proposed by Snowden et al , 283 considering the presence of various different absorbing and non-absorbing polymers, most notably HEC. The simulation incorporates rigid body motion of assembly with both translational and rotational diffusion, which has been shown to significantly influence the assembly structure of nanoparticles.…”
Section: Modelling and Simulation On Assembly Of Nanoparticlessupporting
confidence: 83%
See 1 more Smart Citation
“…To bridge physical experiments and computer simulations, Olson et al recently reported a BD-MC simulation of nanoparticle aggregation in biopolymer matrices using an interparticle potential derived from in situ AFM measurement of surface forces in the HES and HEC solutions. 239 The new AFM-derived potential agrees well with the theoretical interaction model between silica nanoparticles proposed by Snowden et al , 283 considering the presence of various different absorbing and non-absorbing polymers, most notably HEC. The simulation incorporates rigid body motion of assembly with both translational and rotational diffusion, which has been shown to significantly influence the assembly structure of nanoparticles.…”
Section: Modelling and Simulation On Assembly Of Nanoparticlessupporting
confidence: 83%
“…Superhydrophobic network structures of SiO 2 nanoparticles were achieved by Olson et al via solvent mixing in hydroxyethyl cellulose. 239 The rigid chain conformation of hydroxyethyl cellulose was utilized to strategically form flocculated silica nanoparticle assemblies at multiple length scales. Hydroxyethyl starch only formed dispersions of small clusters of nanoparticles.…”
Section: Assembly Via Nanoparticle Blending In Bio...mentioning
confidence: 99%
“…The formation of fractal structures of ZnO was a consequence of two possible mechanisms: (a) HEC chains forming bridges among ZnO nanoparticles, bringing the particles together; (b) large polymer dimensions inducing long-range depletion attractions among nanoparticles. This attraction can induce diffusion-limited aggregation leading to formation of branched fractal assembly structures among ZnO nanoparticles. In another paper, Olson et al demonstrated the influence of assemblies (or fractal structures) of SiO 2 nanoparticles on water resistance (or hydrophobicity) and adhesion performance of biobased polymers of 2-HEC. Using molecular simulations and AFM, Olson et al showed that strong attractions between silica surfaces in the HEC matrix induced diffusion-limited aggregation leading to large-scale fractal assembly structures. These fractal structures imparted superhydrophobic properties to the nanocomposite coatings that significantly improved adhesion, in addition to minimum adhesion loss after prolonged contact with water. Javidparvar et al demonstrated the influence of surface morphology and surface modification of iron oxide nanoparticles on mechanical properties of epoxy coatings.…”
Section: Resultsmentioning
confidence: 99%
“…(1) Olson et al 46 (2) In another paper, Olson et al 45 demonstrated the influence of assemblies (or fractal structures) of SiO 2 nanoparticles on water resistance (or hydrophobicity) and adhesion performance of biobased polymers of 2-HEC. Using molecular simulations and AFM, Olson et al 45 showed that strong attractions between silica surfaces in the HEC matrix induced diffusion-limited aggregation leading to large-scale fractal assembly structures.…”
Section: Some Other Considerationsmentioning
confidence: 99%
See 1 more Smart Citation